2021
DOI: 10.1007/s11606-021-06674-z
|View full text |Cite
|
Sign up to set email alerts
|

A US Population Health Survey on the Impact of COVID-19 Using the EQ-5D-5L

Abstract: Background The COVID-19 pandemic has resulted in negative impacts on the economy, population health, and health-related quality-of-life (HRQoL). Objective To assess the impact of COVID-19 on US population HRQoL using the EQ-5D-5L. Design We surveyed respondents on physical and mental health, demographics, socioeconomics, brief medical history, current COVID-19 status, sleep, dietary, financial, and spending changes. Results were compared to o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 31 publications
7
52
0
Order By: Relevance
“…In our study utility score was lower (0.93) than the general population. This study corroborates with the evidence from the recent EQ-5D studies from China, 8 the USA, 15 Iran, 16 and Switzerland, 17 which reported lower utility value in comparison with the general population. An interesting finding is that men had higher utility scores than women.…”
Section: Discussionsupporting
confidence: 91%
“…In our study utility score was lower (0.93) than the general population. This study corroborates with the evidence from the recent EQ-5D studies from China, 8 the USA, 15 Iran, 16 and Switzerland, 17 which reported lower utility value in comparison with the general population. An interesting finding is that men had higher utility scores than women.…”
Section: Discussionsupporting
confidence: 91%
“…In the general population, there are various studies of post‐COVID‐19 sequelae demonstrating functional disability after recovery. 2 , 3 , 4 Organ transplant recipients are more severely affected by COVID‐19 5 , 6 as compared to the general patients, 7 , 8 , 9 , 10 and hence studies demonstrating long‐term SARS‐CoV‐2 sequelae should trigger an alarm for the need of similar studies in transplant recipients. This entity may require a protocol for post‐COVID‐19 follow‐up and rehabilitation clinic.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument is widely used throughout the world and is available in more than 170 languages [4]. It is feasible to assess the HROoL of the population, given that it is easy to use and intended to provide valid and reliable information [5]. The EuroQol Group perceived a growing interest in assessing HRQOL in younger people, which was a suitable measure for children and adolescents, creating the EQ-5D-Y instrument.…”
Section: Introductionmentioning
confidence: 99%